Fully phased population-prevalent East African cattle BoLA-I alleles determined using PacBio HiFi long-read sequencing represent five novel specificities with distinctive peptide binding potential - Obara, I.; Sandro, A.; Elati, K.; Conneley, T.; Nielsen, M.; Githaka, Naftaly W.; Nanteza, A.; Bishop, Richard P.; Nijhof, A. (Wiley, 2025)
Due to factors such as lower biosecurity, greater wildlife/farm animal interfaces, and environmental challenges, cattle in sub-Saharan Africa are exposed to more diverse and intensive bacterial, viral and protozoan pathogen challenges than cattle in Europe and other high-income regions of the world. Classical class I genes of the major histocompatibility complex (MHC) contribute to protection from diseases caused by these pathogens by refining a huge pool of potential pathogen-derived peptide ligands into a smaller ensemble for presentation to CD8+ T cells. Knowledge of population-prevalent MHC alleles is therefore critical for evidence-based approaches to vaccine design and improved understanding of pathogen resistance. Whereas variation in MHC molecules is understood in most detail for European Bos taurus, the alleles expressed by Africa's cattle remain poorly defined. We have leveraged recent improvements in the accuracy of PacBio high-fidelity (HiFi) circular consensus sequencing (CCS) and adapted stringent sequence filtering algorithms to identify hundreds of as yet uncharacterised fully phased BoLA-I alleles from multiple populations of African taurine (Ankole) and indicine (Zebu) cattle in East Africa. The analysis highlights a convergence of population-prevalent class I MHC allelic repertoires in taurine and indicine cattle, likely due to the similar pathogen-driven selective pressures. Our analysis of the anchor residue accommodating pockets of these prevalent alleles revealed extremely high levels of polymorphism, which contrast with Holstein alleles that exhibit a more limited repertoire of MHC specificity-determining pocket residues, potentially constraining the breadth of peptide presentation. However, in the context of considerable sequence and physicochemical variation in the pocket-forming residues, it was possible to discern overlaps in the predicted peptide binding spectrum. Interrogation of potential differences in peptide binding specificities with European B. taurus alleles revealed that the fully phased African cattle class I MHC alleles represent five novel specificities. We envisage that this novel finding will find broad application in assessing potentially achievable vaccination coverages of future pathogen-encoded vaccine candidates against important intracellular pathogens. One aim of future research should be to leverage recent improvements in the sensitivity of mass spectrometry combined with immunoprecipitation of peptides bound to African cattle MHC to search directly for T-cell epitopes in the context of the inferred ‘supertype’ diversity.